Right ventricular reverse remodeling after pulmonary endarterectomy: magnetic resonance imaging and clinical and right heart catheterization assessment - Berman, Marius (University of Chicago Press, 2014)
Abstract. The objective of this study was to assess the effect of pulmonary endarterectomy (PEA) on right ventricular (RV) reverse remodeling using magnetic resonance imaging (MRI) and to correlate MRI findings with clinical and hemodynamic outcomes postsurgery. We performed a retrospective analysis in 72 patients undergoing PEA surgery in whom MRI and right heart catheterization (RHC) were performed preoperation and 3 months postoperation. RV volumes and mass were assessed by MRI. Continuous variables were expressed as means, changes were compared with a paired t test, and associations between the variables were explored using Pearson correlation coefficients. The mean age was 57 years, and 51% were male. Both RV end-diastolic volume (EDV; 176–117 mL; P < 0.001) and RV end-systolic volume (ESV; 129–64 mL; P < 0.001) reduced significantly following PEA. Preoperative pulmonary artery pressure (PAP) correlated moderately with ESV (r = 0.46, P < 0.001). Postoperatively, PAP correlated with EDV (r = 0.45, P < 0.001) and ESV (r = 0.44, P < 0.001). Moderate correlation was present between hemodynamic parameters: PAP, pulmonary vascular resistance, and right atrial pressure with pre- and postoperation end-systolic and end-diastolic RV mass (P < 0.001). RHC and MRI measurements of cardiac output and RV volumes were significantly different (P < 0.001). In conclusion, RV reverse remodeling, as measured by improvement in RV volumes and mass by MRI, was observed for 3 months in patients who underwent PEA surgery. This is the largest series of patients with pre- and post-PEA MRI assessment so far reported. MRI detects changes in parameters reflecting cardiac remodeling and pulmonary clearance, but measurements are significantly different from those of RHC.